Subalternity and translation: The cultural apparatus of human rights - Nayar, Pramod K. (2011)
What happens when we frame human rights within a cultural context and not just a juridical-political one? This article argues that the cultural apparatus of human rights requires English and translation. This in no way undermines the mother tongue, the vernacular or the local;instead the language of the other enables us to engage with the other so that we reflect upon ourselves. -- Reproduced.
Keywords: Human rights